Pengaruh Testimoni dan Kreasi Nilai Budaya Terhadap Keputusan Pembelian Tiket Bioskop Film Gundala (Sensus Pada Followers Gundala Official) - Nova Audina; Nursyifa Azzahra (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
Screenplays Film is one of the production houses that produce a lot of films, one of which is Gundala. This study discusses how much influence the testimonials and cultural value creation have on the decision to purchase a gundala movie ticket on a gundalaofficial follower diagram. The reason the writer raised this title is because the gundala film successfully penetrated the 44th Toronto International Film Festival. The methodology used in this study is a descriptive and verification method with a quantitative approach. The purpose of this study was to determine the description and measure how much influence the testimonials and the creation of cultural values ??on the decision to purchase Gundala movie tickets